Flow Behaviour Characterization of Hydroxyapatite for Powder Injection Moulding (PIM) / Farrahshaida Mohd Salleh...[et al.] - Mohd Salleh, Farrahshaida; Sulong1, Abu Bakar; Foudzi1, Farhana; Mohamed1, Intan Fadhlina; Azaman1, Natasha Emira; Mas'ood1, Najlaa Nazihah; Seong, Jin Park (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The selection and formulation of binder systems play an important role in powder injection moulding (PIM). The rheological properties of feedstock need to be controlled due to preventing any formation of defects during injection, debinding and sintering. For this study, the Hydroxyapatite (HA) feedstock was prepared by mixing with 40 vol% Palm Stearin (PS) and 60 vol% Polyethelyne (PE) binder system. Three feedstocks (F1, F2 and F3) at different powder loadings of 54, 55 and 56 vol%, respectively, were mixed using brabender mixer. The rheological properties of feedstock such as flow behaviour index, flow activation energy, and mouldability of the feedstocks were determined with a capillary rheometer. It was found that, all feedstocks exhibited pseudoplastic flow, which is an important requirement in PIM. The three feedstock flow behaviour indexes were n (0.16-0.24), and flow activation energies; E at shear rate at 1000s-1 was 5.36, 6.91 and 14.35 kJ/mol. In addition, F3 was found to be able to be injected in a wide range of temperature due to its low-flow behaviour index, low activation energy, and high mouldability index gathered from the rheological test.